Introductory mathematics for economists - Holden, Kenneth; Pearson, Alan Wilfred (London : Macmillan, 1975)
The book introduces to students with a limited mathematical background the essential mathematics needed for a study of economics.
Includes bibliographical references and index.
rpm 13/11/2017
Loans
Keywords: Economics, Mathematical